(untitled) (Filološke studije, 2019)
The article consists of two parts, each written in a different mode though both address the same theme: the relation between the structure (or: internal logic) of Slavic languages on one hand, and some of the most important concepts of Hegel’s Science of Logic on the other hand. The first part introduces the subject in a style which “may appear odd to many readers: too strict to be belletristic, to loose to be science.” It has no explicit but quite a few implicit references (i.e. the sintagm “literary joke” tends to allude to the notorious “Sokal Affair”). The attention is, among other things, directed towards the usage of negation in Slavic languages in footnotes of the Introductive Remark. The Metaphysical Remark, a kind of historico-poetical exercise is what follows next. The crucial point of the discourse is then presented in the Digression: Something, a strict linguistico-logical derivation of the dialectical moment contained in the Slovenian word ‘nekaj’ (i.e. ‘something’), which, as ‘Etwas’, represents a concept “of supreme importance” in Hegel’s Science of Logic. It is shown that ‘nekaj’ in itself, by way of its inherent negation (‘ne-kaj’, lit. ‘not-what’) successfully accommodates the Hegelian concept of Aufhebung. In the Supplement, as the second part of the article is subtitled, some of the above theses are substantiated by an article on the exceptional reception of Hegel’s philosophy in 19th-century Russia, for which a more scientific explanation is now offered: namely, that the Hegelian dialectical logic (at least as far as Aufhebung is it’s key concept) actually represents the internal logic of Slavic languages.